Analisis Controllable Factors 7M Dan Service Quality Dalam Meningkatkan Kualitas Layanan Serta Dampaknya Terhadap Kepuasan Konsumen Di Giant Diponegoro Surabaya - Dwi Krisnara; Mahjudin Mahjudin; Harsono Teguh; Bambang Karnain; Sugiharto Sugiharto; Achmad Daengs GS (Jurnal Mahasiswa Manajemen dan Akuntansi, 2024)
This research is aimed at finding out the influence of Giant Diponegoro Surabaya's marketing management which includes Controllable Factors or controlled factors, and Service Quality or service quality on consumer satisfaction shopping at Giant Diponegoro Surabaya. Thus, the results of this research can at least be used as additional information for management in marketing their products in accordance with consumer desires. With the t-test tool, among the Controllable Factors or controllable factors, Service Quality or service quality is the one that influences the most. are Controllable actors with a percentage of 44.3%, while Service Quality is 37%. After conducting this research, the advice that can be contributed to companies is that company leaders must pay attention to variables with smaller percentages, because in developed countries they are already at the Service Quality stage. which also influences purchasing decisions.